Bismuth(iii)-catalyzed bis-cyclization of propargylic diol-esters: a unified approach for the synthesis of [5,5]- and [6,5]-oxaspirolactones - Kambale, Digambar A.; Borade, Balasaheb R.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2021)
Herein we disclose an unprecedented intramolecular cascade strategy for the construction of alpha,beta-unsaturated [5,5]- and [6,5]-oxaspirolactones that capitalizes on the pi-electrophilic Lewis acid-catalyzed 5-exo-dig or 6-exo-dig mode of cyclization of propargylic diol esters, followed by dehydration and spirolactonization steps. Moreover, semi-protected substrates also delivered the respective oxaspirolactones with the same ease and in appreciable yields under optimal reaction conditions.